2015
DOI: 10.1007/s11524-015-9967-y
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Overdose Deaths in the City and County of San Francisco: Prevalence, Distribution, and Disparities

Abstract: Drug overdose is now the leading cause of unintentional death nationwide, driven by increased prescription opioid overdoses. To better understand urban opioid overdose deaths, this paper examines geographic, demographic, and clinical differences between heroin-related decedents and prescription opioid decedents in San Francisco from 2010 to 2012. During this time period, 331 individuals died from accidental overdose caused by opioids (310 involving prescription opioids and 31 involving heroin). Deaths most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 26 publications
6
73
1
Order By: Relevance
“…As prescribing naloxone was not considered standard practice and lacked the wealth of data supporting most other routine preventive medical interventions, some providers may have opted to not follow the recommendations for naloxone prescribing and vocal “champions” at selected clinics may have been able to substantially influence other providers. With regard to patient-level factors, the median age of opioid overdose death in San Francisco is 50 years,(12) suggesting unmet need for naloxone among older patients. Similarly, Blacks were overrepresented among PMR patients in the safety net clinics (particularly in two of the low-prescribing clinics, representing 88.4% of patients at one and 42.5% of patients at another), as well as among opioid overdose decedents, relative to the San Francisco population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As prescribing naloxone was not considered standard practice and lacked the wealth of data supporting most other routine preventive medical interventions, some providers may have opted to not follow the recommendations for naloxone prescribing and vocal “champions” at selected clinics may have been able to substantially influence other providers. With regard to patient-level factors, the median age of opioid overdose death in San Francisco is 50 years,(12) suggesting unmet need for naloxone among older patients. Similarly, Blacks were overrepresented among PMR patients in the safety net clinics (particularly in two of the low-prescribing clinics, representing 88.4% of patients at one and 42.5% of patients at another), as well as among opioid overdose decedents, relative to the San Francisco population.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Blacks were overrepresented among PMR patients in the safety net clinics (particularly in two of the low-prescribing clinics, representing 88.4% of patients at one and 42.5% of patients at another), as well as among opioid overdose decedents, relative to the San Francisco population. (12) Changes in clinic protocols and additional provider education may be needed to ensure access to naloxone to patients most at risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple ecological and other observational studies of community naloxone distribution programs demonstrated that PWID can learn overdose prevention and administer naloxone successfully (Doe-Simkins, Walley, Epstein, & Moyer, 2009; Green, Heimer, & Grau, 2008; Seal et al, 2003; Seal et al, 2005; Tobin, Sherman, Beilenson, Welsh, & Latkin, 2009), and suggested potential ancillary benefits such as decreased substance use, social connection, and empowerment (Wagner et al, 2014; Wagner et al, 2010). San Francisco documented a dramatic reduction in heroin overdose mortality in the early 2000s, from approximately 180 heroin overdose deaths per year in the late 1990s to 10-11 per year from 2010-2012, although some of that decrease was a result of transitions to prescription opioids (Visconti, Santos, Lemos, Burke, & Coffin, 2015). Scotland's National Naloxone Programme, which started in 2011, was associated with a 36% reduction in the proportion of opioid-related deaths that occurred in the 4 weeks following release from prison (Bird, McAuley, Perry, & Hunter, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…15 Only 10 % of lay naloxone reversals, however, involved opioid analgesics, suggesting that the population reached with traditional naloxone programming was distinct from those at risk for overdose from opioid analgesics. 16 In response, the San Francisco Department of Public Health began offering a naloxone prescription to patients on long-term opioids in selected primary care clinics.…”
Section: Introductionmentioning
confidence: 99%